BEBERAPA TINGGALAN KEPURBAKALAAN ISLAM DI KAWASAN YOGYAKARTA BAGIAN SELATAN: KAITANNYA DENGAN KERAJAAN MATARAM ISLAM - Muhammad Chawari (BRIN, 2003)
From several studies in the southern part of Yogyakarta that were carried out in the form of surveys and excavations by the Balai Arkeologi Yogyakarta starting in 1978, a number of evidences of Islamic heritage have been produced, both in the form of buildings, non-monumental objects, and remnants. After close examination, the chronology of these relics can be found, which date from around the XVI to the XVIII Century, although some data is difficult to determine the actual chronology.